AUTOIMMUNE HYPOTHYROIDISM IN PATIENT WITH NEUROFIBROMATOSIS-1 - Faraz, Ahmed; Nafees, Taha; Ahmed, Syed Arsalan; Rizvi, Shahraiz Shah (Journal of Ayub Medical College Abbottabad, 2015)
A 53 year old woman, diagnosed with Neurofibromatosis I with multiple neurfibromas over trunk, upper limb & lower limb, she had café au lait spots on her abdomen skin. She was admitted to the tertiary care setup with the complains of cold intolerance, numbness in the limbs, high blood pressure & constipation, patient also had complain of weight gain, lab revealed high TSH, low Free thyroid hormones & positive anti thyroglobulin antibodies. Case was diagnosed with autoimmune hypothyroidism. This is the first case reported with such association of these two diseases.